THE POPULAR WILL IN THE CREATION OF THE 1988 FEDERAL CONSTITUTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article addresses the theme of popular will as a fundamental element in the creation of the 1988 Federal Constitution, marking a crucial moment in the political history of Brazil. The promulgation of the 1988 Constitution represented a milestone in the country's transition from a military dictatorship to a democratic regime. The popular will was manifested through a constituent process that involved broad participation from civil society, with the election of members of the National Constituent Assembly directly by the people. In this context, social movements gained significant strength in the search for political, economic and social changes, representing the interests of different groups in society that are at the mercy of the State. Through a hypothetical-deductive study, with a monographic procedure method and the use of legislation, scientific articles and other documents, this research seeks to solve the following problem: how did popular will influence the creation of the 1988 Federal Constitution? Thus, at first, some general considerations will be made about the law as a social will. Subsequently, it will be discussed how the popular will was expressed in the creation of the 1988 Constitution. Finally, a brief analysis of the popular vote, represented by social movements, in the decisions of the Superior Federal Court was carried out.